Vehicle with improved lidar detectable and radar transmission coating

By using retroreflective microspheres, high-deep aspect ratio pigment sheets, and spherical glass beads in the vehicle coating, the problem of insufficient detection capabilities of LIDAR and RADAR signals in the prior art is solved, the detection accuracy and transmittance are improved, and the vehicle is enhanced autonomous driving and safety.

CN119173566APending Publication Date: 2024-12-20INK TECH OPERATING CO
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380038334.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-12
Filing Date
2023-04-13
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing vehicle coatings lack the ability to detect LIDAR and RADAR signals, especially under gloss coatings, which leads to a reduced LIDAR detection accuracy and low transmission of RADAR signals, affecting autonomous driving and safety.

Method used

Using a coating of pigment sheets including retroreflective microspheres and high aspect ratios, the median diameter of the pigment sheet is greater than 35% of the median particle size of the retroreflective microspheres, and spherical glass beads are added to the basecoat to improve the The detection capability of LIDAR and RADAR signals.

Benefits of technology

The detection capability and transmittance of the vehicle under LIDAR and RADAR signals is significantly improved, especially at different incident angles, maintaining good detection performance, enhancing the visibility and three-dimensional image generation ability of the vehicle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119173566A_ABST
    Figure CN119173566A_ABST
Patent Text Reader

Abstract

The present invention relates to a vehicle having a frame or body wherein at least a portion of the outer surface of the frame or body is covered with a coating comprising at least two layers wherein the outer two or three layers are: (a) a base coating; (b) a coloring transparent coating selected according to conditions on the (a); (c) a clear coat top layer on (a) or (b); wherein the bottom coating (a) is composed of an adhesive, spherical glass beads, pigment flakes and optionally selected other components, and the median diameter D50 of the pigment flakes is larger than 35% of the median diameter D50 of the spherical glass beads. The invention further relates to a laser imaging detection and ranging (LIDAR) process of a vehicle, and to a vehicle or a coated substrate comprising said coating in laser imaging detection and ranging (LIDAR) of said vehicle or of said coated substrate; and / or improving the visibility of the vehicle or the coated substrate under visible light conditions; and / or the use of preparing a three-dimensional image of the vehicle or of the coated substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a vehicle having a coating which can be used in light detection and ranging (LIDAR) technology and radio detection and ranging (RADAR) technology. The present invention further relates to a laser imaging detection and ranging process for the vehicle and to the use of the coating on the vehicle or substrate (i) in laser imaging detection and ranging of the coating on the vehicle or substrate, (ii) to improve the visibility of the coating on the vehicle or substrate under visible light conditions and / or (iii) to prepare a three-dimensional image of the coating on the vehicle or substrate. The present invention further relates to a radio detection and ranging process and to the use of spherical glass beads in a coating as a radio wave transmittance improver. Background Art

[0002] Vehicles, such as cars, bicycles, motorcycles and scooters, are often provided with a clear coating top layer to protect the vehicle, for example to prevent oxidation or weathering, and to give the entire coating a glossy appearance. Such a glossy clear coating may be attractive from an aesthetic point of view, but it reduces the detectability of the vehicle using Light Detection and Ranging (LIDAR) technology. In order to correctly determine the distance to the vehicle or the exact outline of the vehicle at different viewing angles using LIDAR technology, an increased Lambertian reflectivity of electromagnetic radiation at the LIDAR wavelength is preferred over specular or retroreflection due to the interfering effects of 100% specular reflection or 100% retroreflection. Lambertian reflectivity is a property that defines an ideal matte or diffuse reflective surface. In this regard, reference may be made to A. Experimental Methods in the Physical Sciences, 46, Chapter 6 - Diffuse Reflectance and Transmittance, 2014, pp. 179 to 219, which is incorporated herein by reference in its entirety. The apparent brightness of a Lambertian surface to an observer is the same regardless of the observer's viewing angle. By definition, 100% Lambertian reflectance defines the whitest white, i.e., the most visible color.

[0003] WO03 / 016964A2 discloses a retroreflective coating system comprising retroreflective microspheres for wet-on-wet application to automotive body panels. It is described that the retroreflective coating system provides satisfactory gloss and retroreflectivity and optimally enhances visibility to others to ensure safety. FIG. 4 of WO03 / 016964A2 describes an embodiment in which a substrate is covered with a base coating BC comprising a binder, retroreflective microspheres and pigments, wherein a clear coating CC is provided on the base coating.

[0004] RADAR sensors are used in vehicles for adaptive cruise control and blind spot, lane change and cross traffic assistance. RADAR sensors for acquiring the surrounding environment are key components of future vehicles with semi-autonomous and fully autonomous driving functionality. Autonomous driving requires RADAR technology that can reliably detect objects in the surrounding area. Automotive RADAR sensors are usually integrated invisibly behind the vehicle bumper. Vehicle bumpers are usually made of plastic with a metallic coating on it, usually the same color as the rest of the car body, including metal flake pigments, such as, for example, aluminum flake pigments. The presence of these metal flake pigments has an adverse effect on the transmission of the coating for RADAR signals.

[0005] It is an object of the present invention to provide a glossy coating for a vehicle, the glossy coating providing improved LIDAR detection capabilities.

[0006] It is an object of the present invention to provide a vehicle with a glossy coating that provides improved transmittance of RADAR signals.

[0007] It is another object of the present invention to provide a glossy coated substrate that provides improved LIDAR detection capabilities.

[0008] Another object of the present invention is to provide a glossy coated substrate that provides improved transmittance of RADAR signals.

[0009] Another object of the present invention is to improve the LIDAR detection capabilities of vehicles. Summary of the invention

[0010] The present inventors have surprisingly discovered that one or more objectives can be achieved by using a coating comprising retroreflective microspheres and pigment flakes having a high aspect ratio, particularly when the ratio of the median diameter D50 of the pigment flakes is greater than 35% of the median particle size D50 of the retroreflective microspheres.

[0011] Thus, in a first aspect, the invention provides a vehicle having a frame or body, wherein at least a portion of the outer surface of the frame or body is covered with a coating, the coating comprising at least two layers, wherein the outer two or three layers are:

[0012] (a) a primer layer;

[0013] (b) an optional tinted clear coat on (a);

[0014] (c) a top layer of a clear coat over (a) or (b);

[0015] Wherein, based on the weight of the primer layer (a), the primer layer (a) consists of:

[0016] 14.95 wt.% to 98.95 wt.% binder;

[0017] 1 to 85 wt.% of spherical glass beads having a median particle size D50 between 1 μm and 150 μm as measured by laser diffraction and having a refractive index between 1.7 and 2.8 measured at a wavelength λ of 589 nm;

[0018] 0.05 wt.% to 30 wt.% pigment flakes selected from the group consisting of metallic pigment flakes, pearlescent pigment flakes, or combinations thereof, the pigment flakes having a median diameter D50 between 1 μm and 75 μm as measured by laser diffraction, a thickness of less than 1 μm, and an aspect ratio (flake diameter / thickness) of at least 10; and

[0019] 0wt.% to 30wt.% other ingredients,

[0020] The median diameter D50 of the pigment flakes is greater than 35% of the median particle diameter D50 of the spherical glass beads.

[0021] The inventors have found that vehicles with the coating have improved LIDAR detection capabilities, particularly at increased angles of incidence, i.e., at increased angles relative to normal incidence. In other words, the coating improves not only the frontal field of view of the vehicle, but also the entire LIDAR scannable profile of the vehicle.

[0022] Furthermore, the inventors have discovered that a vehicle having the coating has improved transmittance to RADAR signals compared to a similar coating that does not include the spherical glass beads. For example, a plastic bumper covered with the coating, as part of the frame or body of the vehicle, has improved transmittance to RADAR signals compared to a plastic bumper covered with a similar coating that does not include the spherical glass beads.

[0023] In a second aspect, the present invention provides a process for laser imaging detection and ranging (LIDAR) of a vehicle as defined herein, the process comprising the following steps:

[0024] (i) providing a LIDAR device including an electromagnetic radiation source, a receiver and, if appropriate, a Global Positioning System (GPS);

[0025] (ii) transmitting electromagnetic radiation from an electromagnetic radiation source of the LIDAR device to the vehicle;

[0026] (iii) scanning electromagnetic radiation reflected by the coating of the vehicle using a receiver of the LIDAR device; and

[0027] (iv) calculating, based on the difference between the transmitted electromagnetic radiation and the scanned reflected electromagnetic radiation, preferably as a function of time, one or more of:

[0028] The distance between the vehicle and the LIDAR device;

[0029] The vehicle’s acceleration;

[0030] The vehicle's deceleration;

[0031] The direction of movement of the vehicle;

[0032] The speed of the vehicle, preferably the speed of the vehicle relative to the speed of the LIDAR device; and

[0033] ·3D image of the vehicle.

[0034] In a third aspect, the present invention provides the use of a vehicle as defined herein or a coated substrate comprising at least two layers, wherein the outer two or three layers are:

[0035] (a) a primer layer;

[0036] (b) an optional tinted clear coat on (a);

[0037] (c) a top layer of a clear coat over (a) or (b);

[0038] Wherein, based on the weight of the primer layer (a), the primer layer (a) consists of:

[0039] 14.95 wt.% to 98.95 wt.% binder;

[0040] 1 to 85 wt.% of spherical glass beads having a median particle size D50 between 1 μm and 150 μm as measured by laser diffraction and having a refractive index between 1.7 and 2.8 measured at a wavelength λ of 589 nm;

[0041] 0.05 wt.% to 30 wt.% pigment flakes selected from the group consisting of metallic pigment flakes, pearlescent pigment flakes, or combinations thereof, the pigment flakes having a median diameter D50 between 1 μm and 75 μm as measured by laser diffraction, a thickness of less than 1 μm, and an aspect ratio (flake diameter / thickness) of at least 10; and

[0042] 0wt.% to 30wt.% other ingredients,

[0043] wherein the median diameter D50 of the pigment flakes is greater than 35% of the median particle diameter D50 of the spherical glass beads,

[0044] in laser imaging detection and ranging (LIDAR) of the vehicle or the coated substrate; and / or

[0045] Improving visibility of the vehicle or the coated substrate under visible light conditions; and / or

[0046] - Preparing a three-dimensional image of the vehicle or the coated substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figures 1A to 1F , FIG. 2A to FIG. 2E and FIG. 3A to FIG. 3D Plotting LIDAR test results of coated substrates. DETAILED DESCRIPTION

[0048] definition

[0049] The term 'pigment' as used herein refers to a particulate colorant such as spherical parts or flakes. The spherical parts or flakes are insoluble in the binder or solvent used.

[0050] The term 'dye' as used herein refers to a colorant that can be dissolved in a molecular form in the binder or solvent used.

[0051] The term 'colorant' as used herein encompasses pigments as well as dyes.

[0052] As used herein, the term 'titanium suboxide' refers to a n O 2n-1 A titanium oxide compound wherein n is an integer greater than 1.

[0053] The term 'LIDAR' is an acronym for 'Light Detection and Ranging' or 'Laser Imaging, Detection and Ranging' and refers to a method for determining the distance to an object (a variable distance), the velocity of an object, and a 3D representation of an object by aiming electromagnetic radiation (usually a laser) at the object and measuring the time it takes for the reflected electromagnetic radiation to return to a receiver.

[0054] The term 'RADAR' is an acronym for 'Radio Detection And Ranging' and refers to a method for determining the range, angle and radial velocity of an object by aiming radio waves at the object and measuring the time it takes for the reflected radio waves to return to a receiver.

[0055] vehicle

[0056] In a first aspect, the invention relates to a vehicle having a frame or body, wherein at least a portion of the outer surface of the frame or body is covered with a coating, the coating comprising at least two layers, wherein the outer two or three layers are:

[0057] (a) a primer layer;

[0058] (b) an optional tinted clear coat on (a);

[0059] (c) a top layer of a clear coat over (a) or (b);

[0060] Wherein, based on the weight of the primer layer (a), the primer layer (a) consists of:

[0061] 14.95 wt.% to 98.95 wt.% binder or resin;

[0062] 1 to 85 wt.% of spherical glass beads having a median particle size D50 between 1 μm and 150 μm as measured by laser diffraction and having a refractive index between 1.7 and 2.8 measured at a wavelength λ of 589 nm;

[0063] 0.05 wt.% to 30 wt.% pigment flakes selected from the group consisting of metallic pigment flakes, pearlescent pigment flakes, or combinations thereof, the pigment flakes having a median diameter D50 between 1 μm and 75 μm as measured by laser diffraction, a thickness of less than 1 μm, and an aspect ratio (flake diameter / thickness) of at least 10; and

[0064] 0wt.% to 30wt.% other ingredients,

[0065] The median diameter D50 of the pigment flakes is greater than 35% of the median particle diameter D50 of the spherical glass beads.

[0066] As is understood by those of ordinary skill in the art, the phrase 'the base coating layer (a) consists of' means that the combined amounts of the binder / resin, spherical glass beads, pigment flakes and other ingredients add up to 100 wt. % of the base coating layer (a).

[0067] As used herein, the term 'vehicle' refers to a physical object used to transport people or goods. In the context of the present invention, non-limiting examples of vehicles are selected from the group consisting of cars, vans, trucks, bicycles, mopeds, scooters, motorcycles, trains, trams, boats, ships, drones, skateboards, missiles, helicopters, and airplanes. In a preferred embodiment, the vehicle is selected from the group consisting of cars, vans, trucks, bicycles, mopeds, scooters, and motorcycles.

[0068] The portion of the exterior surface of the frame or vehicle body to which the coating is applied may be, for example, a metal portion, a carbon fiber portion, a composite portion, a plastic portion, a truck tarp or canvas, and combinations thereof.

[0069] The portion of the exterior surface of the frame or vehicle body to which the coating is applied may be, for example, a metal exterior surface, a carbon fiber exterior surface, a composite exterior surface, a plastic exterior surface, a truck tarp or canvas, and combinations thereof.

[0070] In an embodiment, the portion of the outer surface of the frame or body to which the coating is applied is a plastic portion. In another embodiment, the portion of the outer surface of the frame or body to which the coating is applied is a plastic portion and the pigment flakes are selected from the group consisting of metallic pigment flakes.

[0071] In an embodiment, the coating is applied to at least a portion of the outer surface of the plastic portion of the frame or body. In another embodiment, the coating is applied to at least a portion of the outer surface of the plastic portion of the frame or body, and the pigment flakes are selected from the group consisting of metallic pigment flakes.

[0072] In an embodiment, at least a portion of the frame or body is made of plastic, and at least a portion of its outer surface (i.e., the portion of the frame or body made of plastic) is covered with a coating. In another embodiment, at least a portion of the frame or body is made of plastic, and at least a portion of its outer surface (i.e., the portion of the frame or body made of plastic) is covered with a coating, and the pigment flakes are selected from the group consisting of metallic pigment flakes.

[0073] In an embodiment, more than 1%, preferably more than 10%, more preferably more than 30%, even more preferably more than 50%, still more preferably more than 75%, still more preferably more than 90% of the outer surface of the frame or body is covered with a coating. In an embodiment, the entire outer surface of the frame or body is covered with a coating.

[0074] coating

[0075] As defined above, at least a portion of the outer surface of the frame or body of the vehicle is covered with a coating comprising at least two layers, wherein the outer two or three layers are (a) a basecoat, optionally (b) a tinted clearcoat on (a), and (c) a clearcoat top layer on (a) or (b). Although only the outer two or three layers of the coating are defined, the coating may also include other layers between the outer surface of the frame or body and the basecoat (a).

[0076] For example, when at least a portion of a frame or body of a 'ready-to-use vehicle' has at least two outer layers as described above, the outer surface of the frame or body typically already comprises a primer layer, one or more 'first' basecoat layers different from the basecoat layer (a) and one or more (pigmented) clearcoat (top) layers. The at least two outer layers as defined above are then applied on top of the already existing layers.

[0077] Thus, in an embodiment, the coating comprises the following layers in the following order:

[0078] (i) one or more layers of primer on the outer surface of the frame or body, as the case may be;

[0079] (ii) optionally one or more 'first' primer layers different from primer layer (a) on the outer surface of the frame or body or on (i);

[0080] (iii) one or more clearcoats and / or tinted clearcoats on the outer surface of the frame or body, on (i) or on (ii), as the case may be;

[0081] (iv) a base coating (a) on the outer surface of a frame or vehicle body, on (i), on (ii) or on (iii);

[0082] (v) optionally a pigmented clear coat (b) on the base coat (a); and

[0083] (vi) A clearcoat top layer (c) on the basecoat (a) or on the pigmented clearcoat (b).

[0084] The coating may also be applied to an adherent which is subsequently applied to at least a portion of the outer surface of the frame or body, or, if present, to at least a portion of the outer coating of a different coating already present on the ready-to-use vehicle.

[0085] The term 'primer layer' is well known in the field of paints or coatings for vehicles and relates to an adhesion layer between the substrate to be coated (i.e. the outer surface of the frame or body) and the basecoat (a) or 'first' basecoat. A primer layer is usually applied if the adhesion between the substrate to be coated and the basecoat is insufficient. Therefore, whether a primer layer is useful or even mandatory depends on the nature of the outer surface of the frame or body and the nature of the basecoat.

[0086] The base coating (a) may be the only color providing layer in the coating. In an embodiment, the color is provided only by metallic pigment flakes, pearlescent pigment flakes or a combination thereof. However, the base coating (a) may also include other colorants, such as dyes, organic pigments and inorganic pigments, other than metallic pigment flakes and pearlescent pigment flakes as defined herein.

[0087] If the 'first' primer layer is present below the primer layer (a), this layer is typically a colored primer layer. The first primer layer may include metallic pigment flakes, pearlescent pigment flakes, dyes, organic pigments, inorganic pigments, and combinations thereof. The 'first' primer layer typically does not include spherical glass beads.

[0088] The clear coating top layer (c) and the colored clear coating (b) may comprise two or more layers of (colored) clear coating (top layer) which are superimposed on each other in a subsequent step. The base coating (a) may also comprise two or more layers of base coating which are superimposed on each other in a subsequent step, provided that the entire base coating (a) meets the requirements as defined herein.

[0089] The terms 'clear coat top layer' and 'clear coat' are well known in the art of paints or coatings for vehicles and refer to a clear layer covering a colored base coat, typically free of dyes and pigments. The clear coat top layer serves different purposes, such as protecting the base coat from oxidation or weathering and / or providing a glossy appearance to the entire coating. In a preferred embodiment, the clear coat top layer (c) does not include dyes and pigments. In a preferred embodiment, the clear coat top layer (c) does not include spherical glass beads. The term 'pigmented clear coat' refers to a colored clear coat composition, which is transparent and typically includes dyes, nano-pigments and / or pigment flakes. In a preferred embodiment, the pigmented clear coat (b) does not include spherical glass beads.

[0090] Typically, the types of clearcoat compositions suitable for use in coatings include solvent-based and aqueous clearcoat compositions, powder and powder slurry clearcoat compositions, and thermosetting and thermoplastic clearcoat compositions. The clearcoat composition may be radiation curable. If the clearcoat composition is radiation curable, the clearcoat composition may include a curing initiator, such as a photoinitiator or a thermal initiator.

[0091] In a preferred embodiment, the total thickness of the primer layer (a) is between 1 μm and 300 μm, more preferably between 2 μm and 75 μm, even more preferably between 3 μm and 50 μm, still more preferably between 4 μm and 40 μm, still more preferably between 5 μm and 20 μm. The total thickness of the primer layer (a) is usually not less than the median particle size D90 of the spherical glass beads.

[0092] In a preferred embodiment, the spherical glass beads in the base coating (a) have a median particle size D50 between 1 μm and 25 μm as measured by laser diffraction, and have a refractive index between 1.9 and 2.6 measured at a wavelength λ of 589 nm; the pigment flakes selected from the group consisting of metallic pigment flakes, pearlescent pigment flakes or a combination thereof have a median diameter D50 between 2 μm and 75 μm as measured by laser diffraction, a thickness of less than 1 μm and an aspect ratio (flake diameter / thickness) of at least 10; and the median diameter D50 of the pigment flakes is greater than 35% of the median particle size D50 of the spherical glass beads.

[0093] In a very preferred embodiment, the spherical glass beads in the base coating (a) have a median particle size D50 between 1 μm and 15 μm as measured by laser diffraction, and have a refractive index between 2.0 and 2.3 measured at a wavelength λ of 589 nm; the pigment flakes selected from the group consisting of metallic pigment flakes, pearlescent pigment flakes, or a combination thereof have a median diameter D50 between 3 μm and 75 μm as measured by laser diffraction, a thickness of less than 1 μm, and an aspect ratio (flake diameter / thickness) of at least 10; and the median diameter D50 of the pigment flakes is greater than 45% of the median particle size D50 of the spherical glass beads.

[0094] The present inventors have determined that the improved LIDAR detection capabilities of the present coatings are more pronounced when the coating is metallic and / or has a dark color.

[0095] Adhesive or resin

[0096] Adhesives and resins suitable for use in vehicle coatings are generally known to those of ordinary skill. The suitability of the adhesive and resin type depends not only on its expected wear resistance, but also generally on the manner in which the precursor of the undercoat (a) layer is applied to the vehicle. Precursor undercoat (a) compositions applied in water-based or aqueous form on the one hand, and precursor undercoat (a) compositions applied based on organic solvents on the other hand generally require different adhesives and resins. Adhesives and resins suitable for use in these two types of compositions are well known to those of ordinary skill. The adhesive or resin may be radiation curable. If the adhesive or resin is radiation curable, other ingredients may include a curing initiator, such as a photoinitiator or a thermal initiator.

[0097] Spherical glass beads

[0098] As defined above, the base coating (a) comprises spherical glass beads. In a preferred embodiment, the term 'glass' in 'spherical glass beads' as used herein refers to a non-crystalline, amorphous solid and transparent material made of oxides. In other embodiments, the term 'glass' in 'spherical glass beads' refers to a solid and transparent material made of oxides and containing some microcrystals. The refractive index of spherical glass beads is closely related to the density of glass, although the relationship is not linear. Due to the properties of glass, the density is approximately an additive function of its composition. The density of spherical glass beads with a refractive index between 1.5 and 2.8 is typically 2.5 g / cm 3 With 4.5g / cm 3 Changes between.

[0099] In a preferred embodiment, the spherical glass beads have a refractive index between 1.9 and 2.6, preferably between 2.0 and 2.3, measured at a wavelength λ of 589 nm.

[0100] In another embodiment, the spherical glass beads as defined herein comprise at least two types of spherical glass beads.

[0101] Oxides that can be used for glass are oxides of silicon, boron, aluminum, sodium, barium, vanadium, titanium, lanthanum, strontium, zirconium, potassium, magnesium, iron, calcium, zinc, lithium, barium, and lead. Spherical glass beads may include, for example, silicon dioxide (SiO2), boron oxide (B2O3), phosphorus pentoxide (P2O5), vanadium pentoxide (V2O5), arsenic trioxide (As2O3), germanium oxide (GeO2), calcium oxide (CaO), sodium oxide (Na2O), magnesium oxide (MgO), zinc oxide (ZnO), aluminum oxide (Al2O3), potassium oxide (K2O), iron oxide (Fe2O3), lead oxide (PbO), barium oxide (BaO), barium titanate (BaTiO3), titanium oxide (TiO2), lithium oxide (Li2O), strontium oxide (SrO), lanthanum oxide (La2O3), and zirconium oxide (ZrO2). Silicon dioxide and boron oxide generally have the lowest density. Therefore, glasses containing large weight percentages of these oxides generally produce glass beads with low refractive index. The refractive index can be increased by adding oxides with higher molecular weight. Preferably, the spherical glass beads do not include PbO.

[0102] Glass beads having a refractive index in the range of 1.5-2.51 and their composition in terms of oxides are disclosed in WO2014 / 109564A1, which is incorporated herein by reference in its entirety. PbO-free transparent glass beads having a refractive index above 2.15 are disclosed in US4,082,427, which is incorporated herein by reference in its entirety.

[0103] The spherical glass beads may be colored spherical glass beads as long as they remain transparent. The present invention covers colored spherical glass beads made of colored transparent glass and spherical glass beads provided with a concentric transparent colored coating. The color may be a natural color caused by the composition of the oxide, or may be deliberately selected by adding a component with a specific color. WO2014 / 109564A1 discloses colored glass beads with a high refractive index and high transparency.

[0104] Therefore, in an embodiment, at least a portion of the spherical glass beads are spherical glass beads made of colored transparent glass, and / or at least a portion of the spherical glass beads are provided with a concentric transparent colored coating.

[0105] The spherical glass beads have a median particle size D50 as measured by laser diffraction. Thus, the median particle size D50 is the volume median based on the volume distribution. The median particle size D50 is the diameter below which half of the population of spherical glass beads is located. This volume median particle size is commonly referred to in the art as Dv50 or D v0.5 .

[0106] In a preferred embodiment, the spherical glass beads have a median particle size D50 as measured by laser diffraction between 1.5 μm and 100 μm, more preferably between 2 μm and 50 μm, even more preferably between 2.5 μm and 20 μm, still more preferably between 3 μm and 10 μm (such as between 3 μm and less than 10 μm or between 3 and less than 9.5 μm).

[0107] In another embodiment, the spherical glass beads have a median particle size D50 between 10 μm and 150 μm, such as between 15 μm and 150 μm, between 20 μm and 150 μm, between 25 μm and 150 μm, between 30 μm and 150 μm, or between 35 μm and 150 μm, as measured by laser diffraction.

[0108] In a very preferred embodiment, the spherical glass beads have a median particle size D50 as measured by laser diffraction between 1 μm and 100 μm, such as between 1 μm and 75 μm, between 1 μm and 50 μm, between 1 μm and 45 μm, between 1 μm and 40 μm, between 1 μm and 35 μm, between 1 μm and 30 μm, between 1 μm and 25 μm, between 1 μm and 20 μm, between 1 μm and 15 μm, between 1 μm and 10 μm, between 1 μm and less than 10 μm, between 1 μm and 9.5 μm, between 1 μm and 9 μm, or between 1 μm and 8 μm.

[0109] In a preferred embodiment, the spherical glass beads have a median particle size D50 as measured by laser diffraction between 5 μm and 100 μm, more preferably between 5 μm and 75 μm, even more preferably between 5 μm and 50 μm, such as between 5 μm and 45 μm, between 5 μm and 40 μm, between 5 μm and 35 μm, between 5 μm and 30 μm, between 5 μm and 25 μm, between 5 μm and 20 μm, or between 5 μm and 15 μm.

[0110] Diameters D10 and D90 are commonly referred to in the art as Dv10 or D v0.1 and Dv90 or D v0.9 The D10 diameter is the diameter below which 10% of the population of spherical glass beads lie. Similarly, the D90 diameter is the diameter below which 90% of the population of spherical glass beads lie.

[0111] For example, the span of the particle size distribution of spherical glass beads measured by laser diffraction is defined as:

[0112]

[0113] In another embodiment, the spherical glass beads have a median particle size D50 between 1 μm and 100 μm and a span between 0 and 1.9, preferably between 0 and 1.5, more preferably between 0 and 1, even more preferably between 0 and 0.5 (such as between 0 and 0.2 or between 0 and 0.1) as measured by laser diffraction.

[0114] In a preferred embodiment, the spherical glass beads have a median particle size D50 between 1 μm and 50 μm as measured by laser diffraction and a span between 0 and 1.9, preferably between 0 and 1.5, more preferably between 0 and 1, even more preferably between 0 and 0.5 (such as between 0 and 0.2 or between 0 and 0.1).

[0115] In another preferred embodiment, the spherical glass beads have a median particle size D50 between 1 μm and 25 μm as measured by laser diffraction and a span between 0 and 1.9, preferably between 0 and 1.5, more preferably between 0 and 1, even more preferably between 0 and 0.5 (such as between 0 and 0.2 or between 0 and 0.1).

[0116] In another preferred embodiment, the spherical glass beads have a median particle size D50 between 1 μm and 15 μm as measured by laser diffraction and a span between 0 and 1.9, preferably between 0 and 1.5, more preferably between 0 and 1, even more preferably between 0 and 0.5 (such as between 0 and 0.2 or between 0 and 0.1).

[0117] In yet another preferred embodiment, the spherical glass beads have a median particle size D50 between 1 μm and 10 μm as measured by laser diffraction and a span between 0 and 1.9, such as between 0 and 1.5, between 0 and 1, between 0 and 0.5, between 0 and 0.2, or between 0 and 0.1.

[0118] In yet another preferred embodiment, the spherical glass beads have a median particle size D50 between 1 μm and less than 10 μm as measured by laser diffraction and a span between 0 and 1.9, such as between 0 and 1.5, between 0 and 1, between 0 and 0.5, between 0 and 0.2, or between 0 and 0.1.

[0119] In yet another preferred embodiment, the spherical glass beads have a median particle size D50 between 1 μm and 8 μm as measured by laser diffraction and a span between 0 and 1.9, such as between 0 and 1.5, between 0 and 1, between 0 and 0.5, between 0 and 0.2, or between 0 and 0.1.

[0120] Those skilled in the art will appreciate that span = 0 corresponds to monodisperse spherical glass beads.

[0121] In a preferred embodiment, the spherical glass beads are not hemispherically coated with a light reflecting coating such as for example a hemispherical aluminium coating (HAC).

[0122] In an embodiment, at least a portion of the spherical glass beads are fluorine chemically coated. In another embodiment, at least a portion of the spherical glass beads are silane coated. In another embodiment, at least a portion of the spherical glass beads are silicone coated.

[0123] In a preferred embodiment, the amount of the spherical glass beads is 1.5 wt.% to 80 wt.%, more preferably 2 wt.% to 70 wt.%, even more preferably 3 wt.% to 65 wt.%, based on the weight of the primer layer (a).

[0124] In an embodiment, the amount of the spherical glass beads is 1 wt.% to 80 wt.%, 1 wt.% to 75 wt.%, 1 wt.% to 70 wt.%, 1 wt.% to 65 wt.%, 1 wt.% to 60 wt.%, 1 wt.% to 55 wt.%, 1 wt.% to 50 wt.%, 1 wt.% to 45 wt.%, 1 wt.% to 40 wt.%, 1 wt.% to 35 wt.%, 1 wt.% to 30 wt.%, 1 wt.% to 25 wt.%, 1 wt.% to 20 wt.%, 1 wt.% to 15 wt.%, or 1 wt.% to 10 wt.%.

[0125] In other embodiments, the amount of spherical glass beads is 2 wt.% to 85 wt.%, 5 wt.% to 85 wt.%, 10 wt.% to 85 wt.%, 15 wt.% to 85 wt.%, 20 wt.% to 85 wt.%, 25 wt.% to 85 wt.%, or 30 wt.% to 85 wt.%, based on the weight of the base coating (a).

[0126] Pigment chips

[0127] The basecoat layer (a) comprises between 0.05 wt.% and 30 wt.% of pigment flakes selected from the group consisting of metallic pigment flakes, pearlescent pigment flakes or a combination thereof, based on the weight of the basecoat layer (a), the pigment flakes having a median diameter D50 between 1 μm and 75 μm as measured by laser diffraction, a thickness of less than 1 μm and an aspect ratio (flake diameter / thickness) of at least 10.

[0128] In an embodiment, the pigment flakes are selected from the group consisting of metallic pigment flakes.

[0129] Metallic pigment flakes and pearlescent pigment flakes constitute the two main types of (flaky) special effect pigments. Metallic pigment flakes, also called metallic effect pigment flakes, consist of flake-shaped metal particles and are used to give products metallic effect colors or functional properties such as corrosion protection, heat resistance and electrical conductivity. The small metal flakes behave like mirrors and can reflect incident light. Pearlescent pigment flakes simulate the luster of natural pearls and give the material additional color effects, such as angular color dependence. Pearlescent pigments usually have several layers of materials with different refractive indices. Thin flakes of material with a low refractive index, such as mica, silica, aluminum oxide or glass, are usually used as substrates and coated with high refractive index materials. However, the present invention also covers pearlescent pigment flakes without a substrate.

[0130] In a preferred embodiment, the pearlescent pigment flakes have several layers of materials with different refractive indices, where a low refractive index material, such as mica, silica, alumina or glass, is used as a substrate, and where the substrate is coated with a higher refractive index material.

[0131] Aspect Ratio

[0132] As used herein, the term 'flake' or 'plate' refers to a shape of pigment having a large surface area and a small thickness. Typically, a flake or plate is characterized by its 'aspect ratio', defined as the largest dimension, ie the largest diameter of the surface, divided by the smallest dimension, ie the thickness.

[0133] As used herein, pigment flakes have an aspect ratio of at least 10, preferably at least 15, more preferably at least 20, and even more preferably at least 30.

[0134] In an embodiment, pigment flakes as used herein have an aspect ratio between 10 and 500, preferably between 15 and 250, and more preferably between 20 and 100.

[0135] Median diameter of pigment flakes

[0136] In a preferred embodiment, the median diameter of the pigment flakes is 1.5 μm to 65 μm, more preferably 2 μm to 50 μm, even more preferably 2.5 μm to 40 μm, still more preferably 3 μm to 35 μm, and most preferably 4 μm to 30 μm.

[0137] In another preferred embodiment, the median diameter of the pigment flakes is 1 μm to 65 μm, such as 1 μm to 50 μm, 1 μm to 40 μm, 1 μm to 35 μm, 1 μm to 25 μm, 1 μm to 20 μm, 1 μm to 15 μm or 1 μm to 13 μm.

[0138] In another embodiment, the pigment flakes have a median diameter of 1.5 μm to 75 μm, such as 3 μm to 75 μm, 5 μm to 75 μm, 7 μm to 75 μm, 9 μm to 75 μm, or 11 μm to 75 μm.

[0139] Thickness of pigment flakes

[0140] In a preferred embodiment, the thickness of the pigment flakes is between 10 nm and 950 nm, more preferably between 15 nm and 850 nm, and even more preferably between 50 nm and 650 nm.

[0141] In another preferred embodiment, the thickness of the pigment flakes is between 10 nm and 200 nm, such as between 10 nm and 150 nm, between 10 nm and 100 nm, or between 10 nm and 50 nm.

[0142] In another preferred embodiment, the thickness of the pigment flakes is between 200 nm and 980 nm, such as between 300 nm and 980 nm, between 400 nm and 980 nm, or between 500 nm and 980 nm.

[0143] Types of Pigment Flakes

[0144] In a preferred embodiment, the pigment flakes as defined herein are selected from (A), (B), (C) or a combination thereof:

[0145] (A) a metal sheet or a mica sheet, optionally coated with at least one layer of one or more components selected from the group consisting of metal oxides, metals, metal sulfides, titanium suboxides, titanium oxynitrides, FeO(OH), SiO2, B2O3, GeO2, MgF2, metal alloys, rare earth compounds, and optionally coated with an outer layer comprising one or more colorants and a binder;

[0146] (B) a sheet comprising Al2O3, SiO2, glass, ceramic, graphite or mica plate coated with at least one layer of one or more components selected from the group consisting of metal oxides, metals, metal sulfides, titanium suboxides, titanium oxynitrides, FeO(OH), SiO2, B2O3, GeO2, metal alloys, rare earth compounds, and optionally coated with an outer layer comprising one or more colorants and a binder; and

[0147] (C) Sheet, comprising an Al2O3 plate, doped with one or more components selected from the group consisting of TiO2, ZrO2, SiO2, SnO2, In2O3, ZnO and iron oxide, coated with at least one layer of one or more components selected from the group consisting of metal oxides, metals, metal sulfides, titanium suboxides, titanium oxynitrides, FeO(OH), SiO2, B2O3, GeO2, metal alloys, rare earth compounds, and optionally coated with an outer layer comprising one or more colorants and a binder.

[0148] In a preferred embodiment, the pigment flakes are synthetic pigment flakes. As will be appreciated by those skilled in the art, the term 'synthetic' in 'synthetic pigment flakes' means that the pigment flakes are not naturally occurring pigment flakes, but are instead chemically manufactured pigment flakes or naturally occurring pigment flakes that have been chemically / physically treated. One advantage of using synthetic pigment flakes is that they can produce extremely smooth surfaces and high aspect ratios, thereby improving their reflective properties.

[0149] The pigment flakes (A) may have zero to multiple coating layers, such as 1, 2, 3, 4 or 5 coating layers.

[0150] In an embodiment, the metal in the metallic pigment flake (A) is selected from the group consisting of aluminum, silver and gold, preferably aluminum. In an embodiment, the metallic pigment flake (A) is an aluminum flake without any coating. Examples of aluminum pigment flakes (A) without any coating include Aluminum sheet (Schlenk, Germany). Aluminium pigment flakes typically have a median diameter (D50) between 10 and 15 μm and a thickness of less than 50 nm.

[0151] In an embodiment, the pigment flakes (A) are mica flakes without any coating.

[0152] In an embodiment, the pigment flake (A) is a mica flake having several coatings, such as mica flakes coated with TiO2, Fe2O3 and SnO2. Examples include Silver-Grey SW pigment flakes (Merck, Germany).

[0153] In an embodiment, the metallic pigment flake (A) is an aluminum pigment flake coated with at least one layer of one or more components selected from the group consisting of metal oxides, SiO2, B2O3 and GeO2. In an embodiment, the metallic pigment flake (A) is an aluminum flake coated with a SiO2 layer.

[0154] Examples of suitable aluminum pigment flakes (A) coated with a SiO2 layer are Aluminum sheet (Schlenk, Germany). Aluminum flakes typically have a median diameter (D50) between 5 μm and 50 μm and a thickness between 20 nm and 1 μm.

[0155] Examples of suitable aluminum pigment flakes (A) coated with MgF2 are SpectraFlair pigments (VIAVI Solutions, USA), which typically have a median diameter (D50) between 14 and 35 μm and a thickness between 250 and 900 nm.

[0156] In an embodiment, the flakes (A) are coated with a SiO2 layer and an outer layer comprising one or more colorants and a binder for fixing the one or more colorants. An example of a suitable aluminum pigment flake (A) coated with a SiO2 layer and an outer layer comprising one or more colorants and a binder is a Toyal flake (Toyo Aluminium KK, Japan). The Toyal flakes may have a median diameter (D50) of about 10 μm and a thickness of less than 1 μm (such as about 100 nm).

[0157] Examples of metal oxides that can be applied in the coating on the metallic pigment flakes (A) are selected from the group consisting of TiO2, ZrO2, SnO2, ZnO, MnO2, MgO, Ce2O3, Fe2O3, Fe3O4, FeTiO5, Cr2O3, CoO, CO3O4, VO2, V2O3, NiO, and combinations thereof.

[0158] Examples of suitable aluminum pigment flakes (A) coated with (i) a first layer consisting of SiO2, B2O3, MnO2, MgO, GeO2 or Al2O3, (ii) a second Fe2O3 layer on top of the first layer, and optionally (iii) a third layer of TiO2, ZrO2 or Al2O3 on top of the second layer are disclosed in US2019 / 044679A1, the entire contents of which are incorporated herein by reference.

[0159] Pigment flakes (B) and (C) may have one to more coating layers, such as 2, 3, 4 or 5 coating layers.

[0160] Examples of metal oxides that can be applied in the coating on the metallic pigment flakes (A) are selected from the group consisting of TiO2, ZrO2, SnO2, ZnO, MnO2, MgO, Ce2O3, Fe2O3, Fe3O4, FeTiO5, Cr2O3, CoO, CO3O4, VO2, V2O3, NiO, and combinations thereof.

[0161] In an embodiment, the pigment flake (B) comprises a glass plate, wherein the glass is borosilicate glass. In a highly preferred embodiment, the pigment flake (B) comprises an Al2O3 plate.

[0162] In an embodiment, the pigment flakes (B) or (C) are coated with one or more layers of metal oxides, such as at least one layer of metal oxide selected from the group consisting of TiO2, ZrO2, SnO2, ZnO, MnO2, MgO, Ce2O3, Fe2O3, Fe3O4, FeTiO5, Cr2O3, CoO, CO3O4, VO2, V2O3, NiO, and combinations thereof. In a preferred embodiment, the pigment flakes (B) or (C) are coated with one or more layers of metal oxides selected from the group consisting of TiO2, Fe2O3, Fe3O4, SnO2, ZrO2, Cr2O3, and combinations thereof, such as a layer of metal oxide selected from the group consisting of TiO2, Fe2O3, and combinations thereof.

[0163] An example of a pigment flake (B) comprising an Al2O3 plate coated with different metal oxide layers, a SiO2 layer and an organic dye layer as a top coating is disclosed in EP2799398B1, the entire contents of which are incorporated herein by reference.

[0164] Examples of pigment flakes (B) including Al2O3 plates coated with a metal oxide selected from the group consisting of TiO2, Fe2O3 and combinations thereof and their preparation are disclosed in US Pat. No. 6,267,810B1, the entire contents of which are incorporated herein by reference.

[0165] Examples of pigment flakes (B) comprising Al2O3 plates coated with a TiO2 layer or a Fe2O3 layer are Pigments (Merck, Germany). The pigments typically have a median diameter (D50) between 5 and 50 μm and a thickness of up to 1 μm.

[0166] In another embodiment, the pigment flakes (B) or (C) are coated with a titanium suboxide layer (Ti n O 2n-1, wherein n is an integer greater than 1, such as oxides Ti3O5, Ti2O3), titanium oxynitride layers, FeO(OH) layers or semi-transparent metal thin layers, for example including Al, Fe, Cr, Ag, Au, Pt or Pd or a combination thereof.

[0167] In yet another embodiment, the pigment flakes (B) or (C) are coated with a layer of a metal sulfide, such as a sulfide of tungsten, molybdenum, cerium, lanthanum or a rare earth element.

[0168] In another embodiment, the pigment flakes (B) or (C) are coated with an outer layer of one or more colorants (eg, Prussian blue or carmine) and a binder to secure the colorant.

[0169] As will be appreciated by those skilled in the art, these different layers may be combined as long as the layer of colorant(s) and binder, if present, is always the outer layer.

[0170] Examples of pigment flakes (C) comprising Al2O3 plates doped with titanium oxide and coated with metal oxides and their manufacture are disclosed in EP0763573B1, the entire contents of which are incorporated herein by reference.

[0171] Examples of pigment flakes (C) comprising Al2O3 plates doped with TiO2, ZrO2, SiO2, SnO2, In2O3 or ZnO and coated with metal oxides are disclosed in EP2799398B1, the entire contents of which are incorporated herein by reference.

[0172] Ratio of pigment flake diameter to spherical glass bead diameter

[0173] In a preferred embodiment, the median diameter D50 of the pigment flakes is greater than 36% of the median particle size D50 of the spherical glass beads, more preferably greater than 38%, such as greater than 40%, greater than 45%, greater than 50%, greater than 55%, greater than 60%, greater than 70%, greater than 90%, greater than 110% or greater than 130%.

[0174] In another preferred embodiment, the median diameter D50 of the pigment flakes is between 35% and 400% of the median particle size D50 of the spherical glass beads, and more preferably between 40% and 400%, such as between 45% and 400%, between 50% and 400%, between 55% and 400%, between 60% and 400%, between 70% and 400%, between 90% and 400%, between 110% and 400%, or between 130% and 400%.

[0175] In another embodiment, the median diameter D50 of the pigment flakes is between 35% and 350% of the median particle size D50 of the spherical glass beads, preferably between 35% and 300%, such as between 35% and 250%, between 35% and 225%, between 35% and 200%, between 35% and 175%, between 35% and 150%, between 35% and 125%, between 35% and 100%, or between 35% and 75%.

[0176] Amount of pigment flakes

[0177] In a preferred embodiment, the amount of the pigment flakes in the base coating (a) is 0.1 wt.% to 25 wt.%, such as 0.5 wt.% to 20 wt.%, 1 wt.% to 18 wt.%, 2 wt.% to 16 wt.%, 3 wt.% to 14 wt.%, or 5 wt.% to 13 wt.%, based on the weight of the base coating (a).

[0178] In an embodiment, the amount of the pigment flakes in the base coating (a) is 0.1 wt.% to 24 wt.%, such as 0.1 wt.% to 20 wt.%, 0.1 wt.% to 18 wt.%, 0.1 wt.% to 16 wt.%, 0.1 wt.% to 14 wt.%, or 0.1 wt.% to 13 wt.%, based on the weight of the base coating (a).

[0179] In another embodiment, the amount of the pigment flakes in the base coating (a) is 0.5 wt.% to 30 wt.%, such as 1 wt.% to 30 wt.%, 2 wt.% to 30 wt.%, 5 wt.% to 30 wt.%, 8 wt.% to 30 wt.%, or 10 wt.% to 30 wt.%, based on the weight of the base coating (a).

[0180] The amount of the pigment flakes in the base coating (a) is preferably between 1 part by weight and 1 part by weight and 30 parts by weight of the spherical glass beads, preferably between 1 part by weight and 15 parts by weight of the spherical glass beads, and more preferably between 1 part by weight and 10 parts by weight of the spherical glass beads.

[0181] Other Ingredients

[0182] As defined above, the base coating (a) includes 0 wt.% to 30 wt.% of other ingredients. As will be appreciated by those skilled in the art, the 'other' ingredients are different from the other ingredients defined in the base coating (a). In other words, the other ingredients do not include the binder, the spherical glass beads and the pigment flakes.

[0183] In an embodiment, the other ingredients are selected from the group consisting of thickeners, foam control agents, luminescent agents, UV absorbers, preservatives, dyes, curing initiators, organic pigments, inorganic pigments other than metallic pigment flakes and pearlescent pigment flakes, and combinations thereof.

[0184] In an embodiment, the amount of other ingredients is 0.01wt.% to 25wt.%, 0.02wt.% to 20wt.%, 0.05wt.% to 18wt.%, 0.1wt.% to 16wt.%, 0.2wt.% to 14wt.%, 0.25wt.% to 12wt.%, 0.30wt.% to 10wt.% or 0.35wt.% to 8wt.%, based on the weight of the primer layer (a).

[0185] In an embodiment, the amount of other ingredients is 0wt.% to 25wt.%, 0wt.% to 20wt.%, 0wt.% to 18wt.%, 0wt.% to 16wt.%, 0wt.% to 14wt.%, 0wt.% to 12wt.%, 0wt.% to 10wt.% or 0wt.% to 8wt.%, based on the weight of the primer layer (a).

[0186] In other embodiments, the amount of other ingredients is 0.01 wt.% to 30 wt.%, 0.02 wt.% to 30 wt.%, 0.05 wt.% to 30 wt.%, 0.1 wt.% to 30 wt.%, 0.2 wt.% to 30 wt.%, 0.25 wt.% to 30 wt.%, 0.30 wt.% to 30 wt.%, or 0.35 wt.% to 30 wt.%, based on the weight of the primer layer (a).

[0187] The basecoat layer (a) typically includes one or more thickeners as part of the other ingredients. The thickener can provide the composition to be applied to the vehicle, such as a water-based or organic solvent-based composition, with the rheology required to produce a high-quality basecoat layer (a). Without wishing to be bound by any theory, it is believed that the thickener has no particular advantageous properties in a dried, cured or ready-to-use coating on a vehicle.

[0188] In an embodiment, the other ingredients include a thickener, and the amount of the thickener is 0.01 wt.% to 3 wt.%, preferably 0.01 wt.% to 2 wt.%, even more preferably 0.01 wt.% to 1 wt.%, based on the weight of the base coating (a).

[0189] As will be appreciated by those skilled in the art, the type of thickener present in the basecoat (a) depends on the manner in which the 'precursor basecoat (a) composition' is applied to the vehicle. Precursor compositions applied in water-based or aqueous form on the one hand, and compositions applied based on organic solvents on the other hand, generally require different thickeners to obtain the desired rheological properties.

[0190] Thickener for water-based or aqueous compositions

[0191] A preferred group of thickeners for the aqueous precursor basecoat (a) composition are ASE polymers (alkali swellable emulsions; these polymers are produced using emulsion polymerization). In an embodiment, the hydrophilic monomers of the ASE polymer are selected from the group consisting of (meth)acrylic acid, maleic acid and combinations thereof. In another embodiment, the hydrophobic monomers of the ASE polymer are selected from the group consisting of esters of (meth)acrylic acid with C1 to C4-alcohols, in particular esters of ethyl acrylate, butyl acrylate and methyl methacrylate.

[0192] Another group of preferred thickeners for aqueous precursor basecoat (a) compositions are HASE polymers (hydrophobically modified alkali swellable emulsions; these polymers are produced using emulsion polymerization). The hydrophilic and hydrophobic monomers of the HASE polymers can be the same as those described for the ASE polymers. Preferred hydrophobic associating monomers are (meth)acrylic acid and C8 to C 22 - (meth) acrylate monomers of alcohol and / or (substituted) vinyl alcohol and C8 to C 22 - Vinyl ester monomers of alkyl acids.

[0193] Another group of preferred thickeners for aqueous precursor basecoat (a) compositions are hydrophobically modified ethoxylated urethane (HEUR) polymers. Unlike ASE or HASE type thickeners, HEUR polymers are nonionic and soluble at any pH. This solubility is attributed to the ethylene oxide backbone of the polymer, which is water soluble and makes up the majority of the polymer structure. Therefore, HEUR polymers require a hydrophobic portion in the composition to interact with the ethylene oxide backbone to impart structure.

[0194] Examples of ASE polymers include 1125 (available from BASF), ACULYN TM 33; ACULYN TM 38. ACUSOL TM 810A、ACUSOL TM 830、ACUSOL TM 835、ACUSOL TM 842 (all available from DOW Chemical) and Aqua 30 polymer (available from Lubrizol Corporation).

[0195] Examples of HASE polymers include ACULYN TM Excel, ACRYSOL TM TT615、ACULYN TM 22; ACULYN TM 88. ACUSOL TM 801S、ACUSOL TM 805S、ACUSOL TM 820 and ACUSOL TM 823 (all available from DOW Chemical).

[0196] Examples of HEUR polymers include ACUSOL TM 880、ACUSOL TM 882、ACULYN TM 44 and ACULYN TM 46N (all available from DOW Chemical).

[0197] In another embodiment, the thickener for the aqueous precursor basecoat (a) composition is selected from the group consisting of ASE polymers, HASE polymers, HEUR polymers, liquid acrylic crosslinked or copolymer dispersions, acrylate crosslinked polymers, crosslinked polyacrylic acid polymers, crosslinked polyacrylic acid copolymers, modified ethylene vinyl acetate copolymer waxes, modified ureas or non-ionic aqueous emulsions of urea-modified polyamides, and combinations thereof.

[0198] Thickeners for organic solvent-based compositions

[0199] Examples of thickeners that can be used in the organic solvent-based precursor basecoat (a) composition are preferably selected from the group consisting of (modified) hydrogenated castor oil, clay, modified clay, calcium sulfonate complex, organophilic phyllosilicate, silica gel, synthetic amorphous silica, acrylic gelling agent, modified cellulose material, polyurea dispersion, urea-modified polyamide solution, polyurethane dispersion and combinations thereof. Examples of modified clay include LT and 38 (Elementis Global). Examples of silica gel include N20 (Wacker Chemical) or (Evonik). Examples of organophilic phyllosilicates include Claytone 40 (Byk). Examples of modified hydrogenated castor oils are RM 1900 (BASF). An example of hydrogenated castor oil is RM 1920 (BASF). An example of a solution of a urea-modified nonpolar polyamide in isobutanol / monophenyl glycol is Rheobyk-431 (Byk). An example of a solution of a medium-polar urea-modified polyamide in isobutanol / solvent naphtha is Rheobyk-430 (Byk). An example of a synthetic amorphous silica is (Huber).

[0200] In a preferred embodiment, the organic solvent-based precursor base coating (a) composition includes two thickeners, more preferably:

[0201] Organophilic phyllosilicates and modified hydrogenated castor oil; or

[0202] Calcium sulfonate complex and polyurea dispersion.

[0203] Preferred thickeners in the base coat (a)

[0204] In a preferred embodiment, the base coating (a) includes one or more thickeners as part of the other ingredients selected from the group consisting of: ASE polymers, HASE polymers, HEUR polymers, liquid acrylic cross-linked or copolymer dispersions, acrylate cross-linked polymers, cross-linked polyacrylic acid polymers, cross-linked polyacrylic acid copolymers, non-ionic aqueous emulsions of modified ethylene vinyl acetate copolymer waxes, modified urea or urea-modified polyamides, (modified) hydrogenated castor oil, clay, modified clay, calcium sulfonate complexes, organophilic phyllosilicates, silica gels, synthetic amorphous silica, acrylic gelling agents, modified cellulosic materials, polyurea dispersions, urea-modified polyamide solutions, polyurethane dispersions, and combinations thereof.

[0205] Laser Imaging Detection And Ranging (LIDAR) Technology

[0206] A second aspect of the invention relates to a process for laser imaging detection and ranging (LIDAR) of a vehicle as defined herein, the process comprising the following steps:

[0207] (i) providing a LIDAR device including an electromagnetic radiation source, a receiver and, if appropriate, a Global Positioning System (GPS);

[0208] (ii) transmitting electromagnetic radiation from an electromagnetic radiation source of the LIDAR device to the vehicle;

[0209] (iii) scanning electromagnetic radiation reflected by the coating of the vehicle using a receiver of the LIDAR device; and

[0210] (iv) calculating, based on the difference between the transmitted electromagnetic radiation and the scanned reflected electromagnetic radiation, preferably as a function of time, one or more of:

[0211] The distance between the vehicle and the LIDAR device;

[0212] The vehicle’s acceleration;

[0213] The vehicle's deceleration;

[0214] The direction of movement of the vehicle;

[0215] The speed of the vehicle, preferably the speed of the vehicle relative to the speed of the LIDAR device; and

[0216] ·3D image of the vehicle.

[0217] As will be appreciated by those skilled in the art, calculating the speed, acceleration, deceleration and direction of movement of the vehicle requires steps (ii) and (iii) to be performed as a function of time.

[0218] If the LIDAR device is also equipped with GPS, the distance between the vehicle and the LIDAR device can also be indicated on the map, and the 3D image of the vehicle can be marked on the map.

[0219] In a preferred embodiment, the electromagnetic radiation transmitted and scanned in steps (ii) and (iii) respectively has a wavelength between 740nm and 2500nm, preferably between 750nm and 1800nm, more preferably between 780nm and 1600nm, such as 905nm or 1550nm.

[0220] In an embodiment, the electromagnetic radiation transmitted and scanned in steps (ii) and (iii) respectively has a wavelength between 740nm and 2200nm, such as between 740nm and 2000nm, between 740nm and 1800nm, between 740nm and 1700nm, between 740nm and 1650nm and between 740nm and 1600nm.

[0221] In another embodiment, the electromagnetic radiation transmitted and scanned in steps (ii) and (iii) respectively has a wavelength between 750nm and 2500nm, such as between 780nm and 2500nm, between 800nm ​​and 2500nm, between 825nm and 2500nm, between 850nm and 2500nm, and between 875nm and 2500nm.

[0222] The LIDAR device may for example be a mobile device, such as a LIDAR gun for checking vehicle speed, a device fixed to some infrastructure element, for example to determine traffic density, or a mobile device located in another vehicle.

[0223] Radio Detection and Ranging (RADAR) Technology

[0224] Another aspect of the present invention relates to a radio detection and ranging (RADAR) process, comprising the following steps:

[0225] (i) providing a vehicle as defined above with a RADAR device within the frame or body, the RADAR device comprising a radio wave source and a receiver, and wherein the vehicle optionally includes a Global Positioning System (GPS);

[0226] (ii) transmitting radio waves from a radio wave source of the RADAR device through at least a portion of the outer surface of the frame or body of the vehicle covered with the coating as defined above to an object external to the vehicle;

[0227] (iii) using a receiver of a RADAR device to scan radio waves reflected by objects outside the vehicle; and

[0228] (iv) calculating, based on the difference between the transmitted radio waves and the scanned reflected radio waves, preferably as a function of time, one or more of:

[0229] The distance between the object and the RADAR device;

[0230] The acceleration of the object relative to the RADAR device;

[0231] The deceleration of the object relative to the RADAR device;

[0232] The direction in which the object is moving relative to the RADAR device; and

[0233] The speed of the object, preferably the speed of the object relative to the speed of the RADAR device.

[0234] The phrase 'RADAR device within a frame or body' as used herein implies that the frame or body is located between the RADAR device and objects outside the vehicle, such as a RADAR device located behind a bumper inside a vehicle to scan objects in front of the bumper outside the vehicle.

[0235] In the RADAR process, the portion of the outer surface of the frame or body to which the coating is applied is a plastic portion, such as a plastic bumper. In a preferred embodiment of the RADAR process, the portion of the outer surface of the frame or body to which the coating is applied is a plastic portion, such as a plastic bumper, and the pigment flakes are selected from the group consisting of metallic pigment flakes. The RADAR device including the radio wave source and the receiver is preferably located inside the frame or body behind the plastic bumper of the vehicle.

[0236] In the RADAR process, the portion of the outer surface of the frame or body to which the coating is applied is the outer surface of a plastic part, such as the outer surface of a plastic bumper. In a preferred embodiment of the RADAR process, the portion of the outer surface of the frame or body to which the coating is applied is the outer surface of a plastic part, such as the outer surface of a plastic bumper, and the pigment flakes are selected from the group consisting of metallic pigment flakes. The RADAR device including the radio wave source and the receiver is preferably located in the frame or body behind the plastic bumper of the vehicle.

[0237] As will be appreciated by those skilled in the art, calculating the velocity, acceleration, deceleration and direction of movement of an object requires steps (ii) and (iii) to be performed as a function of time.

[0238] The distance between objects and the RADAR device can be processed into a (real-time) image of the vehicle's surroundings to be shown on a video screen inside the vehicle.

[0239] If the vehicle is also equipped with GPS, the distance between the object and the RADAR device can also be indicated on the map.

[0240] In a preferred embodiment, the radio waves transmitted and scanned in steps (ii) and (iii) have wavelengths between 3.5 mm and 14.5 mm, respectively. In another preferred embodiment, the radio waves transmitted and scanned in steps (ii) and (iii) have wavelengths between 12.1 mm and 12.6 mm, respectively (short-range RADAR; SRR). In yet another preferred embodiment, the radio waves transmitted and scanned in steps (ii) and (iii) have wavelengths between 3.6 mm and 4.0 mm, respectively (long-range RADAR; LRR).

[0241] Process for coating the outer surface of a vehicle frame or body

[0242] The basecoat (a) is usually provided to the outer surface of the frame or body of the vehicle in the form of an organic solvent-based composition or in the form of an aqueous or water-based composition. This composition is hereinafter referred to as the 'precursor basecoat (a) composition'.

[0243] Therefore, these organic solvent-based, aqueous or water-based precursor undercoat (a) compositions, in addition to the solid components of the undercoat (a) in relative amounts as defined above, also include a solvent. The amount of solvent in the organic solvent-based, aqueous or water-based composition is typically 15 wt.% to 75 wt.%, such as 25 wt.% to 65 wt.%, based on the weight of the precursor undercoat (a) composition.

[0244] In other words, the precursor undercoat layer (a) composition may consist of the following, based on the weight of the precursor undercoat layer (a) composition:

[0245] (A) 15 wt.% to 75 wt.% of water, aqueous solvent or organic solvent; and

[0246] (B) 25 wt.% to 85 wt.% of a solid composition,

[0247] Wherein, based on the weight of the solid composition (B), the solid composition (B) consists of:

[0248] 14.95 wt.% to 98.95 wt.% binder;

[0249] 1 wt.% to 85 wt.% spherical glass beads having a median particle size D50 between 1 μm and 150 μm as measured by laser diffraction and having a refractive index between 1.7 and 2.8 measured at a wavelength λ of 589 nm;

[0250] 0.05 wt.% to 30 wt.% pigment flakes selected from the group consisting of metallic pigment flakes, pearlescent pigment flakes, or a combination thereof, said pigment flakes having a median diameter D50 between 1 μm and 75 μm as measured by laser diffraction, a thickness less than 1 μm, and an aspect ratio (flake diameter / thickness) of at least 10; and

[0251] 0wt.% to 30wt.% other ingredients,

[0252] The median diameter D50 of the pigment flakes is greater than 35% of the median particle diameter D50 of the spherical glass beads.

[0253] The solvent may be, for example, an aqueous solvent or water. The term 'aqueous solvent' as used herein relates to a solvent comprising at least 70 wt.% water, preferably at least 80 wt.% water, more preferably at least 90 wt.% water, even more preferably at least 95 wt.% water, such as at least 96 wt.%, at least 97 wt.% or at least 98 wt.% by weight of the aqueous solvent. The remaining solvent in the aqueous solvent is not particularly limited, but is generally an organic solvent miscible with water, such as an alcohol (e.g., methanol, ethanol, propanol, isopropanol, butanol, isobutanol, secondary butanol, tertiary butanol, pentanol, hexanol, cyclohexanol); a polyol (e.g., ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, butanediol, hexanediol, pentanediol, glycerol, hexanetriol or thiodiglycol); a glycol derivative, such as, for example, an ether or an ester (e.g., ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monobutyl ethyl ether, propylene glycol monomethyl ether, propylene glycol monobutyl methyl ether, dipropylene glycol monoethyl ether, triethylene glycol monomethyl ether, ethylene glycol diacetate, ethylene glycol monomethyl ether acetate, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether or ethylene glycol monophenyl ether); amines (e.g., ethanolamine, diethanolamine, triethanolamine, N-methyldiethanolamine, N-ethyldiethanolamine, morpholine, N-ethylmorpholine, ethylenediamine, diethylenetriamine, triethylenetetramine, polyethyleneimine or tetramethylpropylenediamine); amides (e.g., formamide, N,N-dimethylformamide or N,N-dimethylacetamide), dimethyl sulfoxide, sulfolane, 2-pyrrolidone, N-methyl-2-pyrrolidone, N-vinyl-2-pyrrolidone, 2-oxazolidinone, l,3-dimethyl-2-imidooxadiazolidinone, acetonitrile, acetone and combinations thereof.

[0254] The organic solvent may be a mixture of organic solvents. Preferred organic solvents are selected from the group consisting of aliphatic and aromatic solvents, ketones, esters, glycidyl ethers, alcohols, halogenated hydrocarbons and combinations thereof. Excellent organic solvents are selected from the group consisting of xylene (mixture of isomers), toluene, ethylbenzene, naphtha, 1,2,4-trimethylbenzene, sym-trimethylbenzene, n-propylbenzene, isoamyl acetate, n-butyl acetate, (2-methoxymethylethoxy)propanol, 2-butoxyethyl acetate, 2-methylbutyl acetate, isobutanol, 1-butanol, 1-ethoxypropan-2-ol, 2,6-dimethyl-4-heptanone, 2-methoxy-1-methylethyl acetate, 4,6-dimethyl-heptane-2-one, 4-methyl-2-pentanone, 1-methoxy-2-propanol, 1-methoxy-2-propyl acetate, 2-(2-butoxyethoxy)ethanol, 2-butoxyethanol, 5-methylhexane-2-one, ethyl acetate, and combinations thereof.

[0255] Alternatively, the 'precursor basecoat (a) composition' may also be a reactive system, wherein the solvent comprises a liquid reactive organic monomer, such as a low molecular weight acrylate, and wherein the binder comprises a reactive higher molecular weight organic resin, which may be dispersed or dissolved in the solvent. Thus, both the solvent and the resin may constitute the liquid phase in the precursor basecoat (a) composition, and may together form the binder in the basecoat (a) when cured.

[0256] In one aspect, the invention relates to a process for coating at least a portion of an outer surface of a frame or body of a vehicle, the process comprising the steps of:

[0257] i) providing a vehicle having a frame or body having an outer surface, wherein at least a portion of the outer surface may have contained a different coating;

[0258] ii) applying a precursor basecoat (a) composition as defined above to at least a portion of the outer surface of the frame or vehicle body of step (i), or to the outer coating of the different coatings of step (i), to provide a precursor basecoat (a);

[0259] iii) optionally at least partially drying and curing the precursor basecoat layer (a) of step (ii) to provide a basecoat layer (a);

[0260] iv) optionally applying a precursor colored clear coating (b) composition onto at least a portion of the precursor base coating (a) of step (ii), or onto at least a portion of the base coating (a) of step (iii) to provide a precursor colored clear coating (b), optionally followed by at least partial drying and curing to provide a colored clear coating (b);

[0261] v) applying the precursor clear coating (c) composition to at least a portion of the precursor base coating (a) of step (ii), to at least a portion of the base coating (a) of step (iii), to the precursor colored clear coating (b) of step (iv), or to the colored clear coating (b) of step (iv), followed by drying and curing to provide a clear coating top layer (c).

[0262] The step (ii) of applying the precursor basecoat (a) composition may comprise applying a single layer in one step or placing multiple layers on top of each other in subsequent steps. The subsequent layers may be applied 'wet-on-wet', which means that the subsequent layer is applied onto the previous layer, at least some to almost all of the solvent in the layer is evaporated, but the layer is not (completely) cured. This means that even when the subsequent layers are applied 'wet-on-wet', an intermediate drying step is applied between the application of the subsequent layers.

[0263] It is also possible to completely dry and cure a layer before applying a subsequent layer. The selection of appropriate drying conditions is within the skill of a person skilled in the art.

[0264] In an embodiment, step (ii) encompasses applying more than one layer, such as 2, 3, 4 or 5 layers.

[0265] In an embodiment, step (ii) encompasses n subsequent steps producing n layers, and wherein layer x is at least partially applied onto layer x-1, wherein x is an integer between 2 and n, and wherein n is an integer between 2 and 5.

[0266] Steps (iv) and (v) of applying the precursor (pigmented) clearcoat composition may comprise applying a single layer in one step or placing multiple layers on top of each other in subsequent steps. The subsequent layers may be applied 'wet-on-wet', meaning that the subsequent layer is applied onto the previous layer without (completely) drying or curing the layer.

[0267] In an embodiment, the precursor clearcoat (c) composition applied in step (v) is applied over a layer that is not fully dried or cured, ie, a 'wet-on-wet' application. The selection of appropriate drying conditions is within the skill of a person skilled in the art.

[0268] The geometry of the outer surface of the frame or body to be coated is not limited in any sense, as long as it can be coated, for example, by spraying. In an embodiment, the outer surface of the frame or body to be coated is flat. In other embodiments, the outer surface of the frame or body to be coated is curved. In other embodiments, the outer surface of the frame or body to be coated includes flat portions and curved portions.

[0269] Step (ii) of applying the precursor basecoat (a) composition is preferably performed using powder coating, electrostatic atomization, curtain coating, spray gun, high-speed rotating clock, high-speed rotating disk or using a spray can with a propellant. In a preferred embodiment, spraying is performed without using a propellant.

[0270] In another preferred embodiment, the outer two or three coatings as defined above can be applied to an adherent which is subsequently applied to at least a portion of the outer surface of the frame or body, or, if present, to at least a portion of the outer coating of a different coating already present on the vehicle.

[0271] use

[0272] In a third aspect, the invention relates to the use of a vehicle or a coated substrate as defined herein, wherein the coating comprises at least two layers, wherein the outer two or three layers are:

[0273] (a) a primer layer;

[0274] (b) an optional tinted clear coat on (a);

[0275] (c) a top layer of a clear coat over (a) or (b);

[0276] Wherein, based on the weight of the primer layer (a), the primer layer (a) consists of:

[0277] 14.95 wt.% to 98.95 wt.% binder;

[0278] 1 to 85 wt.% of spherical glass beads having a median particle size D50 between 1 μm and 150 μm as measured by laser diffraction and having a refractive index between 1.7 and 2.8 measured at a wavelength λ of 589 nm;

[0279] 0.05 wt.% to 30 wt.% pigment flakes selected from the group consisting of metallic pigment flakes, pearlescent pigment flakes, or combinations thereof, the pigment flakes having a median diameter D50 between 1 μm and 75 μm as measured by laser diffraction, a thickness of less than 1 μm, and an aspect ratio (flake diameter / thickness) of at least 10; and

[0280] 0wt.% to 30wt.% other ingredients,

[0281] wherein the median diameter D50 of the pigment flakes is greater than 35% of the median particle diameter D50 of the spherical glass beads,

[0282] in laser imaging detection and ranging (LIDAR) of the vehicle or the coated substrate; and / or

[0283] Improving visibility of the vehicle or the coated substrate under visible light conditions; and / or

[0284] - Preparing a three-dimensional image of the vehicle or the coated substrate.

[0285] In another aspect, the present invention relates to the use of spherical glass beads as transmission improvers for radio waves in a coating comprising a binder and metal pigment flakes, the spherical glass beads having a median particle size D50 between 1 μm and 150 μm as measured by laser diffraction, and having a refractive index between 1.7 and 2.8 measured at a wavelength λ of 589 nm, the metal pigment flakes having a median diameter D50 between 2 μm and 75 μm as measured by laser diffraction, a thickness of less than 1 μm and an aspect ratio (flake diameter / thickness) of at least 10, wherein the median diameter D50 of the metal pigment flakes is greater than 35% of the median particle size D50 of the spherical glass beads.

[0286] Preferred embodiments defined in the context of the first, second and third aspects also apply to this other aspect.

[0287] Other Implementations

[0288] In a fourth aspect, the invention relates to a vehicle or a coated substrate having a frame or a body, wherein at least a portion of the outer surface of the frame or body is covered with a coating, the coating comprising at least two layers, wherein the coating comprises at least two layers, wherein the outer two or three layers are:

[0289] (a) a primer layer;

[0290] (b) an optional tinted clear coat on (a);

[0291] (c) a top layer of a clear coat over (a) or (b);

[0292] Wherein, based on the weight of the primer layer (a), the primer layer (a) consists of:

[0293] 14.95 wt.% to 98.95 wt.% binder;

[0294] 1 to 85 wt.% of spherical glass beads having a median particle size D50 between 1 μm and less than 10 μm as measured by laser diffraction and having a refractive index between 1.7 and 2.8 measured at a wavelength λ of 589 nm;

[0295] 0.05 wt.% to 30 wt.% pigment flakes selected from the group consisting of metallic pigment flakes, pearlescent pigment flakes, or combinations thereof, the pigment flakes having a median diameter D50 between 1 μm and 75 μm as measured by laser diffraction, a thickness of less than 1 μm, and an aspect ratio (flake diameter / thickness) of at least 10; and

[0296] · 0 wt.% to 30 wt.% other ingredients.

[0297] In a fifth aspect, the present invention relates to a laser imaging detection and ranging (LIDAR) process for a vehicle as defined in the fourth aspect, the process comprising the following steps:

[0298] (i) providing a LIDAR device including an electromagnetic radiation source, a receiver and, if appropriate, a Global Positioning System (GPS);

[0299] (ii) transmitting electromagnetic radiation from an electromagnetic radiation source of the LIDAR device to the vehicle;

[0300] (iii) scanning electromagnetic radiation reflected by the coating of the vehicle using a receiver of the LIDAR device; and

[0301] (iv) calculating, based on the difference between the transmitted electromagnetic radiation and the scanned reflected electromagnetic radiation, preferably as a function of time, one or more of:

[0302] The distance between the vehicle and the LIDAR device;

[0303] The vehicle’s acceleration;

[0304] The vehicle's deceleration;

[0305] The direction of movement of the vehicle;

[0306] The speed of the vehicle, preferably the speed of the vehicle relative to the speed of the LIDAR device; and

[0307] ·3D image of the vehicle.

[0308] Another aspect of the present invention relates to a radio detection and ranging (RADAR) process, comprising the following steps:

[0309] (i) providing a vehicle as defined in the fourth aspect with a RADAR device within the frame or body, the RADAR device comprising a radio wave source and a receiver, and wherein the vehicle optionally includes a Global Positioning System (GPS);

[0310] (ii) transmitting radio waves from a radio wave source of the RADAR device through at least a portion of the outer surface of the frame or body of the vehicle covered with the coating as defined in the fourth aspect to an object outside the vehicle;

[0311] (iii) using a receiver of a RADAR device to scan radio waves reflected by objects outside the vehicle; and

[0312] (iv) calculating, based on the difference between the transmitted radio waves and the scanned reflected radio waves, preferably as a function of time, one or more of:

[0313] The distance between the object and the RADAR device;

[0314] The acceleration of the object relative to the RADAR device;

[0315] The deceleration of the object relative to the RADAR device;

[0316] The direction in which the object is moving relative to the RADAR device; and

[0317] The speed of the object, preferably the speed of the object relative to the speed of the RADAR device.

[0318] In a sixth aspect, the present invention relates to the use of a vehicle or a coated substrate as defined in the fourth aspect:

[0319] in laser imaging detection and ranging (LIDAR) of the vehicle or the coated substrate; and / or

[0320] Improving visibility of the vehicle or the coated substrate under visible light conditions; and / or

[0321] - Preparing a three-dimensional image of the vehicle or the coated substrate.

[0322] In another aspect, the invention relates to the use of spherical glass beads as transmission improvers for radio waves in a coating comprising a binder and metal pigment flakes, the spherical glass beads having a median particle size D50 between 1 μm and 150 μm as measured by laser diffraction, and having a refractive index between 1.7 and 2.8 measured at a wavelength λ of 589 nm, the metal pigment flakes having a median diameter D50 between 2 μm and 75 μm as measured by laser diffraction, a thickness of less than 1 μm and an aspect ratio (flake diameter / thickness) of at least 10.

[0323] Preferred embodiments defined in the context of the first, second and third aspects also apply to the fourth, fifth and sixth aspects.

[0324] Thus, the invention has been described with reference to certain embodiments discussed above. It will be appreciated that these embodiments are susceptible to various modifications and alternative forms well known to those skilled in the art.

[0325] Furthermore, for a proper understanding of this document and its claims, it should be understood that the verb 'comprise' and its conjugations are used in its non-restrictive sense, meaning that the items following the word are included, but items not specifically mentioned are not excluded. Furthermore, unless the context clearly requires that there is one and only one element, the use of the indefinite article 'a' or 'an' to refer to an element does not exclude the possibility that more than one element is present. The indefinite article 'a' or 'an' usually means 'at least one'.

[0326] Examples

[0327] Material

[0328] Spherical glass beads

[0329] Micro glass beads (AL), obtained from Jiangxi Shengfulai Retroreflective Materials Co., Ltd., China, having a refractive index of about 2.2 measured at a wavelength λ of 589 nm, a median particle size D50 of 40.4 μm, a D10 diameter of 37.3 μm, and a D90 diameter of 44.1 μm as measured by laser diffraction.

[0330] Micro glass beads (AS), obtained from Jiangxi Shengfulai Retroreflective Materials Co., Ltd., China, have a refractive index of about 2.2 measured at a wavelength λ of 589 nm, a median particle size D50 of 20 μm, a D10 diameter of 16.3 μm, and a D90 diameter of 26.2 μm as measured by laser diffraction.

[0331] • Micro glass beads (BS), obtained from Swarco, Austria, having a refractive index of about 2.1 measured at a wavelength λ of 589 nm, with a median particle size D50 of 5 μm and a D90 diameter of 10 μm as measured by laser diffraction.

[0332] • Micro glass beads (CL), obtained from Jiangxi Shengfulai Retroreflective Materials Co., Ltd., China, having a refractive index of about 1.9 measured at a wavelength λ of 589 nm, a median particle size D50 of 40.4 μm, a D10 diameter of 34.9 μm, and a D90 diameter of 44 μm as measured by laser diffraction.

[0333] Micro glass beads (CS), obtained from Jiangxi Shengfulai Retroreflective Materials Co., Ltd., China, have a refractive index of about 1.9 measured at a wavelength λ of 589 nm, a median particle size D50 of 20 μm, a D10 diameter of 14.7 μm, and a D90 diameter of 25.1 μm as measured by laser diffraction.

[0334] Solvents

[0335] Softened water

[0336] Syrox S900 adhesive, Syrox S941 viscosity reducer, ACULYN TM Excel, PC 2000 and Solvent part of MBL

[0337] Other Ingredients

[0338] · Solid portion of PC 2000, obtained from Angus Chemical Company; Neutralizer

[0339] · Solid portion of MBL, obtained from Thor; preservative

[0340] ·ACULYN TMExcel solids from DOW Chemical, HASE thickener

[0341] Adhesives

[0342] Solids portion of Syrox S900 adhesive and Syrox S941 viscosity reducer, obtained from Axalta Coating Systems pigment flakes

[0343] · T60-10 SW Crystal Silver, from Merck KGaA, coated with Al2O3 flakes, with a median diameter (D50) of about 18 μm, a thickness of less than 1 μm, and an aspect ratio (flake diameter / thickness) greater than 10 (Al2O3, TiO2, SnO2)

[0344] · T61-10 WNT Crystal Silver, from Merck KGaA, coated with Al2O3 flakes, with a median diameter (D50) of about 11 μm, a thickness of less than 1 μm, and an aspect ratio (flake diameter / thickness) greater than 10 (Al2O3, TiO2, SnO2)

[0345] · 9602 Silver-Grey SW, obtained from Merck Performance Materials Germany GmbH, having a median diameter (D50) of 22.3 μm, a thickness of less than 1 μm, and an aspect ratio (sheet diameter / thickness) of greater than 10 (mica, TiO2, F2O3, and SnO2)

[0346] · 9612 Silver-Grey Fine Satin SW, available from Merck Performance Materials Germany GmbH, with a median diameter (D50) of 7.2 μm, a thickness of less than 1 μm, and an aspect ratio (sheet diameter / thickness) greater than 10 (mica, TiO2, F2O3, and SnO2)

[0347] Clear coating composition

[0348] S5000 HS Top Clear / S6000 HS Activator Slow, clearcoat precursor compositions, available from Axalta Coating Systems

[0349] Composition

[0350] Twelve aqueous precursor basecoat (a) compositions having different types of spherical glass beads and different types of pigment flakes were prepared as follows.

[0351] In the first step, for each type of spherical glass beads, an 'intermediate composition' was prepared by adding the following ingredients (see 'Materials' section) to a container at ambient temperature (about 20°C) in the following order: (1) demineralized water, (2) a preservative MBL, (3) spherical glass beads, (4) pH adjustment PC 2000 neutralizer and (5) ACULYN TM Excel thickener. The resulting mixture was stirred in a Dispermill Orange-line 18 / 186 at ambient temperature for approximately 5 minutes.

[0352] Twelve aqueous precursor base coating (a) compositions were prepared by placing Syrox S900 binder, Syrox S941 viscosity reducing agent, different types of pigment flakes (see the 'Materials' section) and the intermediate composition described above in a beaker, followed by thorough mixing with Dispermill Orange-line 18 / 186 at ambient temperature (about 20° C.) for 5 to 10 minutes. The types and amounts (wt.%, based on the weight of the aqueous precursor base coating (a) composition) of the ingredients in the different aqueous precursor base coating (a) compositions are shown in Tables 1 and 2. Tables 1 and 2 also list the ratio [%] of the median diameter D50 of the pigment flakes to the median particle diameter D50 of the spherical glass beads in the different aqueous precursor base coating (a) compositions.

[0353] Table 1: Waterborne precursor base coating (a) composition

[0354]

[0355]

[0356] (*)Solvent portion of this ingredient

[0357] (#) Solids content of the ingredient (§) MBL, PC 2000 and ACULYN TM Solvent section of Excel

[0358] Table 2: Aqueous Precursor Base Coating (a) Composition

[0359]

[0360]

[0361] (*)Solvent portion of this ingredient

[0362] (#) Solids content of the ingredient

[0363] (§) MBL, PC 2000 and ACULYN TM Solvent section of Excel

[0364] Example 1

[0365] All aqueous precursor basecoat (a) compositions were applied to flat white metal test panels (10.5 x 14.9 cm) with vertical black stripes (0.3 cm wide) on the surface using a spray gun (DV1.2 Mini) with a 1.2 mm nozzle at ambient temperature (about 20°C). Two types of layers were applied: a 'normal layer' and a 'fog layer'. For the 'normal layer', the spray gun was located 30 to 40 cm from the metal test panel and a pressure of 2.0 bar was applied. For the 'fog layer', the spray gun was located 40 to 50 cm from the metal test panel and a pressure of 1.5 bar was applied. The fog layer is a very thin layer of droplets (i.e., not a complete layer) applied first to improve adhesion.

[0366] Drying is applied between the application of subsequent 'normal layers'. Some aqueous precursor basecoat (a) compositions are applied to metal test panels as a mist layer, followed by drying with a subsequent normal layer on top of the mist layer, followed by drying, and a clear topcoat is applied again, followed by drying ('single basecoat' or '1L'). Other aqueous precursor basecoat (a) compositions are applied to metal test panels as a mist layer with two subsequent normal layers, with intermediate drying and final drying, and by applying a clear topcoat again, followed by drying ('double basecoat' or '2L'). The transparent clearcoat top layer consists of a clearcoat composition as defined in the 'materials' section. In summary, the coated substrate consists of a metal test panel, a mist layer on top of the metal test panel, one or two basecoats on top of the mist layer, and a final transparent clearcoat top layer.

[0367] The compositions of the dried base coating (a) are shown in Tables 3 and 4. Tables 3 and 4 also list the ratio [%] of the median diameter D50 of the pigment flakes to the median particle diameter D50 of the spherical glass beads in different dried compositions.

[0368] Table 3: Primer (a) composition

[0369]

[0370]

[0371] (#) Solids content of the ingredient

[0372] Table 4: Primer (a) composition

[0373]

[0374]

[0375] (#) Solids content of the ingredient

[0376] The LIDAR detection capability was determined by scanning the surface of the coated metal test panel with a Livox Tele-15 LIDAR device (Livox Technology Company Co., Ltd) at a wavelength of 905 nm at an angle of about 0 degrees (i.e., in a direction perpendicular to the coated surface). The scanning was performed under daylight conditions. The Tele-15 LIDAR device was placed at a distance of about 20 meters from the surface of the coated metal test panel. The Tele-15 LIDAR device calculated the reflectivity values ​​of different areas of the surface of the scanned coated metal test panel based on the ratio of the reflected laser energy to the incident laser energy, and generated a point cloud based on these data. Each point in the point cloud has a corresponding reflectivity value between 0 and 255. In the Lambertian reflectance model, reflectivity values ​​between 0 and 155 correspond to reflectivity in the range of 0 to 100%, while values ​​between 151 and 255 correspond to retroreflection. Lambertian reflectivity is a property that defines an ideal matte or diffuse reflective surface. The apparent brightness of a Lambertian surface to an observer is the same regardless of the observer's viewing angle. Therefore, the increase of the Lambertian reflectivity of a surface is very important in LIDAR applications because it allows the detection of complete objects at different viewing angles.

[0377] A histogram is created by counting all points in the point cloud that have reflectivity values ​​in the range of 1 to 10, in the range of 11 to 20, in the range of 21 to 30, etc. The number counts for each range are then normalized based on the total number of points in the point cloud and expressed as a percentage.

[0378] Table 5 lists the different coated metal test panels tested, the ratio [%] of the median diameter D50 of the pigment flakes to the median particle diameter D50 of the spherical glass beads, the number of basecoats (a) applied and a graph showing the histogram.

[0379] Table 5: LIDAR test on coated white metal test panel (approximately 0°)

[0380]

[0381]

[0382] according to Figures 1A to 1FIt can be concluded that all coated metal substrates show considerable LIDAR detection capabilities at an angle of about 0 degrees (ie, in a direction perpendicular to the coated surface).

[0383] The more the 'main body' of the histogram is shifted towards higher reflectivity values, the better the LIDAR detection capability of the coated metal substrate. Figures 1A to 1F It can be seen that as the ratio of the median diameter D50 of the pigment flakes to the median particle size D50 of the spherical glass beads increases, the 'main body' of the histogram shifts towards higher reflectance values.

[0384] Thus, the present inventors unexpectedly discovered that LIDAR detection capability improves at higher ratios of the median diameter D50 of the pigment flakes to the median particle size D50 of the spherical glass beads.

[0385] Example 2

[0386] The LIDAR detection capability of the coated white metal test panels prepared as described in Example 1 was determined by scanning the surface of the coated metal test panels at a wavelength of 905 nm at an angle of 15 degrees using a Livox Tele-15 LIDAR device (Livox Technology Company Co., Ltd). Table 6 lists the different coated metal test panels tested, the ratio [%] of the median diameter D50 of the pigment flakes to the median particle diameter D50 of the spherical glass beads, the number of basecoats (a) applied, and a graph showing the histogram.

[0387] Table 6: LIDAR test on light grey coated metal test panel (approximately 15°)

[0388] Examples Base coating ratio[%] Metal Sheet Degree[°] layer picture 2a #13 90 White 15 DL 2A 2b #18 55 White 15 DL 2A 2c #13 90 White 15 SL 2B 2d #18 55 White 15 SL 2B 2e #14 45 White 15 DL 2C 2f #19 27 White 15 DL 2C 2g #14 45 White 15 SL 2D 2h #19 27 White 15 SL 2D 2i #4 55 White 15 DL 2E 2j #9 18 White 15 DL 2E

[0389] according to FIG. 2A to FIG. 2E It can be concluded that all coated metal substrates show considerable LIDAR detection capabilities even at an angle of 15 degrees. FIG. 2A to FIG. 2E It can also be seen that as the ratio of the median diameter D50 of the pigment flakes to the median particle size D50 of the spherical glass beads increases, the 'main body' of the histogram shifts to higher reflectance values. Thus, the inventors unexpectedly discovered that even at an angle of 15 degrees, LIDAR detection capability improves at higher ratios of the median diameter D50 of the pigment flakes to the median particle size D50 of the spherical glass beads.

[0390] Example 3

[0391] The LIDAR detection capability of a coated metal test panel prepared as described in Example 1 but now with a vertical black stripe (0.3 cm wide) across the surface on a gray metal test panel (10.5×14.9 cm) was determined by scanning the surface of the coated metal test panel at a wavelength of 905 nm at an angle of about 0 degrees using a Livox Tele-15 LIDAR device (Livox Technology Company Co., Ltd). Table 7 lists the different coated metal test panels tested, the ratio [%] of the median diameter D50 of the pigment flakes to the median particle diameter D50 of the spherical glass beads, the number of basecoats (a) applied, and a graph showing the histogram.

[0392] Table 7: LIDAR test on dark grey coated metal test panel (0°)

[0393] Examples Base coating ratio[%] Metal Sheet Degree[°] layer picture 3a #13 90 grey 0 DL 3A 3b #18 55 grey 0 DL 3A 3c #14 45 grey 0 DL 3B 3d #19 27 grey 0 DL 3B 3e #15 257 grey 0 DL 3C 3f #20 157 grey 0 DL 3C 3g #4 55 grey 0 DL 3D 3h #9 18 grey 0 DL 3D

[0394] according to FIG. 3A to FIG. 3D It can be concluded that all coated metal substrates show considerable LIDAR detection capabilities at an angle of about 0 degrees (ie, in a direction perpendicular to the coated surface).

[0395] According to separate FIG. 3A to FIG. 3D It can also be seen that as the ratio of the median diameter D50 of the pigment flakes to the median particle size D50 of the spherical glass beads increases, the 'main body' of the histogram shifts towards higher reflectance values. Figure 1A and Figure 3A Comparison Figure 1C and Figure 3B Comparison and Figure 1F and Figure 3C A comparison of can infer that the shift is more pronounced when coating darker substrates.

Claims

1. A vehicle having a frame or body, wherein at least a portion of the outer surface of the frame or body is covered with a coating, the coating comprising at least two layers, wherein the outer two or three layers are: (a) a primer layer; (b) an optional tinted clear coat on (a); (c) a top layer of a clear coat over (a) or (b); Wherein, based on the weight of the primer layer (a), the primer layer (a) consists of: 14.95 wt.% to 98.95 wt.% binder; 1 to 85 wt.% of spherical glass beads having a median particle size D50 between 1 μm and 150 μm as measured with laser diffraction and having a refractive index between 1.7 and 2.8 measured at a wavelength λ of 589 nm; 0.05 wt.% to 30 wt.% pigment flakes selected from the group consisting of metallic pigment flakes, pearlescent pigment flakes, or a combination thereof, the pigment flakes having a median diameter D50 between 2 μm and 75 μm as measured by laser diffraction, a thickness of less than 1 μm, and an aspect ratio (flake diameter / thickness) of at least 10; and 0wt.% to 30wt.% other ingredients, The median diameter D50 of the pigment flakes is greater than 35% of the median particle diameter D50 of the spherical glass beads.

2. The vehicle as claimed in claim 1, wherein the amount of the pigment flakes selected from the group consisting of metallic pigment flakes, pearlescent pigment flakes or a combination thereof in the base coating (a) is between 1 part by weight and 1 part by weight and 30 parts by weight of the spherical glass beads, preferably between 1 part by weight and 15 parts by weight of the spherical glass beads, and more preferably between 1 part by weight and 10 parts by weight of the spherical glass beads.

3. A vehicle as described in claim 1 or 2, wherein the median diameter D50 of the pigment flakes selected from the group consisting of metallic pigment flakes, pearlescent pigment flakes or a combination thereof in the base coating (a) is greater than 36% of the median particle size D50 of the spherical glass beads, preferably greater than 38%, such as greater than 40%, greater than 45%, greater than 50%, greater than 55%, greater than 60%, greater than 70%, greater than 90%, greater than 110% or greater than 130%.

4. The vehicle according to any one of claims 1 to 3, wherein the spherical glass beads in the base coating (a) have a refractive index between 1.9 and 2.6, preferably between 2.0 and 2.3, measured at a wavelength λ of 589 nm.

5. The vehicle according to any one of claims 1 to 4, wherein the spherical glass beads in the base coating (a) have a median particle size D50 as measured by laser diffraction of between 1.5 μm and 100 μm, preferably between 2 μm and 50 μm, even better between 2.5 μm and 20 μm, still better between 3 μm and 10 μm.

6. The vehicle according to any one of claims 1 to 5, wherein the other ingredients in the base coating (a) are selected from the group consisting of thickeners, foam control agents, luminescent agents, UV absorbers, preservatives, dyes, curing initiators, organic pigments, inorganic pigments other than the metallic pigment flakes and pearlescent pigment flakes, and combinations thereof.

7. The vehicle of any one of claims 1 to 6, wherein the metallic pigment flakes and pearlescent pigment flakes are selected from the group consisting of: (A) Metallic pigment flakes or mica pigment flakes, optionally coated with at least one layer of one or more components selected from the group consisting of metal oxides, metals, metal sulfides, titanium suboxides, titanium oxynitrides, FeO(OH), SiO2, B2O3, GeO2, MgF2, metal alloys, rare earth compounds, and optionally coated with an outer layer comprising one or more colorants and a binder; (B) Pigment flakes comprising Al2O3, SiO2, glass, ceramic, graphite or mica sheets coated with at least one layer of one or more components selected from the group consisting of metal oxides, metals, metal sulfides, titanium suboxides, titanium oxynitrides, FeO(OH), SiO2, B2O3, GeO2, metal alloys, rare earth compounds, and optionally coated with an outer layer comprising one or more colorants and a binder; (C) Pigment flakes comprising Al2O3 plates doped with one or more components selected from the group consisting of TiO2, ZrO2, SiO2, SnO2, In2O3, ZnO and iron oxide, coated with at least one layer of one or more components selected from the group consisting of metal oxides, metals, metal sulfides, titanium suboxides, titanium oxynitrides, FeO(OH), SiO2, B2O3, GeO2, metal alloys, rare earth compounds, and optionally coated with an outer layer comprising one or more colorants and a binder.

8. The vehicle of any one of claims 1 to 7, wherein the coating comprises the following layers in the following order: (i) one or more layers of primer on said outer surface of said frame or body, as the case may be; (ii) one or more 'first' primer layers different from primer layer (a) on said outer surface of said frame or body or on (i), as the case may be; (iii) one or more clearcoats and / or tinted clearcoats on said outer surface of said frame or body, on (i) or on (ii), as the case may be; (iv) said base coating (a) on said outer surface of said frame or vehicle body, on (i), on (ii) or on (iii); (v) optionally a pigmented clear coat (b) on the base coat (a); and (vi) said clearcoat top layer (c) on the basecoat (a) or on the pigmented clearcoat (b).

9. The vehicle according to any one of claims 1 to 8, wherein the total thickness of the base coating (a) is between 1 μm and 300 μm.

10. The vehicle of any one of claims 1 to 9, wherein more than 1%, preferably more than 10%, more preferably more than 30%, even more preferably more than 50%, still more preferably more than 75%, still more preferably more than 90% of the outer surface of the frame or body is covered with the coating.

11. The vehicle of any one of claims 1 to 10, selected from the group consisting of a car, a van, a truck, a bicycle, a moped, a scooter, a motorcycle, a train, a tram, a boat, a ship, a drone, a skateboard, a missile, a helicopter and an airplane.

12. A laser imaging detection and ranging (LIDAR) process for a vehicle as claimed in any one of claims 1 to 11, the process comprising the following steps: (i) providing a LIDAR device comprising an electromagnetic radiation source, a receiver and, if appropriate, a global positioning system (GPS); (ii) transmitting electromagnetic radiation from the electromagnetic radiation source of the LIDAR device to the vehicle; (iii) scanning, using the receiver of the LIDAR device, the electromagnetic radiation reflected by the coating of the vehicle; and (iv) calculating, from said difference between said transmitted electromagnetic radiation and said scanned reflected electromagnetic radiation, preferably as a function of time, one or more of: the distance between the vehicle and the LIDAR device; the acceleration of the vehicle; the deceleration of the vehicle; the moving direction of the vehicle; the speed of the vehicle, preferably the speed of the vehicle relative to the speed of the LIDAR device; and A 3D image of the vehicle.

13. Use of a vehicle or a coated substrate as claimed in any one of claims 1 to 11, wherein the coating comprises at least two layers, wherein the outer two or three layers are: (a) a primer layer; (b) an optional tinted clear coat on (a); (c) a top layer of a clear coat over (a) or (b); Wherein, based on the weight of the primer layer (a), the primer layer (a) consists of: 14.95 wt.% to 98.95 wt.% binder; 1 to 85 wt.% of spherical glass beads having a median particle size D50 between 1 μm and 150 μm as measured by laser diffraction and having a refractive index between 1.7 and 2.8 measured at a wavelength λ of 589 nm; 0.05 wt.% to 30 wt.% pigment flakes selected from the group consisting of metallic pigment flakes, pearlescent pigment flakes, or a combination thereof, the pigment flakes having a median diameter D50 between 1 μm and 75 μm as measured by laser diffraction, a thickness of less than 1 μm, and an aspect ratio (flake diameter / thickness) of at least 10; and 0wt.% to 30wt.% other ingredients, wherein the median diameter D50 of the pigment flakes is greater than 35% of the median particle diameter D50 of the spherical glass beads, in laser imaging detection and ranging (LIDAR) of the vehicle or the coated substrate; and / or Improving the visibility of the vehicle or the coated substrate under visible light conditions; and / or - Preparing a three-dimensional image of the vehicle or the coated substrate.

14. The LIDAR process of claim 12 or the use of claim 13, wherein the LIDAR uses electromagnetic radiation having a wavelength between 740 nm and 2500 nm, preferably between 750 nm and 1600 nm, such as 905 nm or 1550 nm.

Citation Information

Patent Citations

  • Flaky aluminum oxide and pearlescent pigment, and production thereof

    EP0763573B1

  • alpha-Alumina flakes

    EP2799398B1

  • Joint determination of demodulation and channel state information reference signals

    US20190044679A1

  • High refractive index glass compositions

    US4082427A

  • Pigment mixture

    US6267810B1